Numerical Simulation of Long-Wave Infrared Generation Using an External Cavity Diamond Raman Laser - Chen, Hui; Bai, Zhenxu; Zhao, Chen; Yang, Xuezong; Ding, Jie; Qi, Yaoyao; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2021)
Diamond has a broad spectral transmission range (>0.2 μm) and the largest Raman frequency shift (1332 cm-1) among known Raman crystals. Hence, the diamond Raman laser has the potential to achieve lasing in the long-wave infrared (LWIR) range, which is difficult to reach via other crystalline lasers. Here, we report a new approach to achieve LWIR output using diamond Raman conversion and provide the corresponding analysis model and simulation results. The conversion efficiency is analyzed as function of the pump waist size, output-coupler transmission, and crystal length, at constant pump power. The maximum output power at which a diamond of relatively large size can be operated without damage is predicted. This study paves a way for high-power LWIR lasing in diamond.